2008
DOI: 10.1002/nme.2315
|View full text |Cite
|
Sign up to set email alerts
|

Automatic adaptive FE analysis of thin‐walled structures using 3D solid elements

Abstract: In this study, a new automatic adaptive refinement procedure for thin‐walled structures using 3D solid elements is suggested. This procedure employs a specially designed superconvergent patch recovery (SPR) procedure for stress recovery, the Zienkiewicz and Zhu (Z–Z) error estimator for the a posteriori error estimation, a new refinement strategy for new element size prediction and a special mesh generator for adaptive mesh generation. The proposed procedure is different from other schemes in such a way that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…However, this validates the fact that using the X-FEM do not modify the performance of the underlying finite element approach. Note also that, as explained in [1], the large increase of the error in the case of a 16 aspect ratio with tetrahedrons is due to an insufficient discretization in the plane of the plate.…”
Section: Thin Structurementioning
confidence: 81%
See 2 more Smart Citations
“…However, this validates the fact that using the X-FEM do not modify the performance of the underlying finite element approach. Note also that, as explained in [1], the large increase of the error in the case of a 16 aspect ratio with tetrahedrons is due to an insufficient discretization in the plane of the plate.…”
Section: Thin Structurementioning
confidence: 81%
“…An intermediate possibility for the use of solid elements was proposed by Lee and Xu [39,1] for applications in offshore structures where both thin and thick plates coexist. Performing a cost study for quadratic and cubic approximations, the authors deduced that quadratic elements were a good compromise between computational cost and accuracy [15,16].…”
Section: The Extended Finite Element Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a typical model for a 2.5 m long section, 45,000 brick elements are employed in the FE analysis. Note that in the previous study (Lee and Xu 2008), it is shown that 4 layers of element in the thickness direction is sufficient to capture the stress variation in the thickness 41 direction while the computational cost incurred is still within an acceptable limit for the parametric study discussed in Section 4. In order to obtain accurate modelling results but maintain computational efficiency, smaller elements are employed in critical areas like the corners and the free web middle part as shown in Figure 4.3.…”
Section: Model Descriptionmentioning
confidence: 89%